Do Lehmann cholesteric droplets subjected to a temperature gradient rotate as rigid bodies?. Issue 9 (1st February 2016) - Poy, Guilhem; Oswald, Patrick
Abstract : We show that Lehmann cholesteric droplets submitted to a temperature gradient never rotate as a solid, whatever their internal texture. Abstract : We performed a Fluorescence Recovery After Photobleaching (FRAP) experiment during the Lehmann rotation of cholesteric droplets in thermodynamic coexistence with the isotropic liquid and subjected to a temperature gradient. By creating and tracking bleached spots near the surface of banded droplets (in which the cholesteric helix is perpendicular to the gradient) and concentric circle droplets oriented by an electric field (in which the helix is parallel to the gradient), we found that neither type of droplet rotates as a solid. This result shows that the texture rotation is mainly due to the local director rotation.